Morphological Character and Conserved Region of Elongation Factor 1? (EF1?) Gene Analysis in Lepidotrigona terminata - Suprianto, Suprianto; Trianto, Manap; Alam, Nur; Kirana, Ni Gusti Ayu Galuh Candra (Metamorfosa: Journal of Biological Sciences, 2020)
Lepidotrigona terminata is one of the stingless bees of the Apidae family. Morphological characteristics of L. terminata species are very rare due to their genetic characteristics. The elongation factor 1? gene has been studied in the growth and development of both morphology and molecular systematics. This study aims to describe the morphological character of L. terminata from Temanggung Regency, Central Java with a purposive sampling method and analyze the conserved gene elongation factor 1? area to explain genetic variation based on the proportion of DNA bases analyzed in silico and computational methods using a database in GenBank with number access DQ813123.1, DQ813125.1 and DQ813124.1. The results of the analysis explained that the morphological character of L. terminata is very difficult to distinguish from several other Lepidotrigona groups and it is suspected that the genetic trait of the elongation factor 1? gene has an influence on the morphological character of L. terminata . The proportion of DNA bases of the target gene has a length of about 682 bp to 780 bp with the highest proportion of bases found in Adenine (A) around 216 bp (31.67%) to 251 bp (32.18%), the least number of bases found in Guanin (G) around 121 bp (17.74%) to 140 bp (17.95%) and has twelve conserved gene regions. The data obtained from the research provide basic information to study the morphological characteristics and conserved regions of the elongation factor 1? gene in L. terminata . keywords: L. terminata , morphology, elongation factor 1?, in silico , computational methods